(untitled) (Khairulummah, 2022)
Marriage is a process that is concerned with most of the adults in every society of the world. It is a bond between individuals that every individual strive to strenghten so that the life of the bonding partners becomes a cradle of peace and contentment. Despite the differences in nature, if the spouses are trained religiously and psychologically, they can live a peaceful life because in such a case, they will not consider the difference in moods as stubbornness and obstinacy. Rather, they will consider it as a natural phenomenon and behave accordingly with their spouse. By following this approach, the couple will enjoy a happy married life. In such matters, an insight about the teachings of the Prophet (peace be upon him) is indispensable. This is because the teachings of the Prophet (peace be upon him) are effective to shape behaviors of the spouses in a prudent manner and align those behaviors with the human psychology. If the instructions of the Prophet (peace be upon him) are practiced appropriately, the married life becomes a source of happiness despite the prevalence of differences in the behaviors of the spouses. In such manner, the spouses not only follows the religious spirit but also enjoy a successful married life.